2014
DOI: 10.1159/000362521
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar Lavage Cellular Patterns in Monoclonal Antibody-Induced Lung Disease

Abstract: Background: The increase in the use of monoclonal antibodies (mAB) as a targeted therapy for a variety of diseases has been accompanied by an increase in reports of interstitial lung abnormalities in treated patients. Objective: Bronchoalveolar lavage (BAL) is routinely performed in these patients to rule out infection, so we sought to determine the BAL cellular pattern in individuals with mAB-induced lung disease (mAB-ILD). Methods: We utilized a case-control study design. Among patients treated with mAB, cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Gupta et al untersuchten an einem Kollektiv von 29 Patienten die BAL bei Verdacht auf eine durch Antikörpertherapie induzierte Lungenerkrankung. Die Differenzialzytologie zeigte in erster Linie eine vermehrte Lymphozytenexpression [13]. Die alveoläre Lymphozytose ist allerdings letztlich unspezifisch.…”
Section: Resultsunclassified
“…Gupta et al untersuchten an einem Kollektiv von 29 Patienten die BAL bei Verdacht auf eine durch Antikörpertherapie induzierte Lungenerkrankung. Die Differenzialzytologie zeigte in erster Linie eine vermehrte Lymphozytenexpression [13]. Die alveoläre Lymphozytose ist allerdings letztlich unspezifisch.…”
Section: Resultsunclassified
“…Investigators found that mixed inflammation with moderate lymphocytic and mild neutrophilic alveolitis is the most common BAL cellular pattern in patients with ILD. Such findings may be useful for the early identification of monoclonal antibodies-ILD [50].…”
Section: Drug-induced Ildsmentioning
confidence: 91%
“…Bronchoalveolar lavage (BAL) is an established diagnostic tool in variable types of ILD that supports the clinical diagnosis not only in adults but also in children [24,25,26,27]. The objective of this study was to analyze VEGF and ferritin levels in BALF samples in children with different types of ILD: hypersensitivity pneumonitis (HP), idiopathic interstitial pneumonia (IIP) and idiopathic pulmonary hemosiderosis (IPH).…”
Section: Introductionmentioning
confidence: 99%